Alterations of plant architecture and phase transition by the phytoplasma virulence factor SAP11. (28th August 2018) - Chang, Shu Heng; Tan, Choon Meng; Wu, Chih-Tang; Lin, Tzu-Hsiang; Jiang, Shin-Ying; Liu, Ren-Ci; Tsai, Ming-Chen; Su, Li-Wen; Yang, Jun-Yi
Abstract : Phytoplasma SAP11 effectors acquired fundamental activity in destabilizing TB/CYC-TCPs, the key factors controlling axillary meristem development, and serve as core virulence factors responsible for the witches' broom symptom. Abstract: As key mediators linking developmental processes with plant immunity, TCP (TEOSINTE-BRANCHED, CYCLOIDEA, PROLIFERATION FACTOR 1 and 2) transcription factors have been increasingly shown to be targets of pathogenic effectors. We report here that TB/CYC (TEOSINTE-BRANCHED/CYCLOIDEA)-TCPs are destabilized by phytoplasma SAP11 effectors, leading to the proliferation of axillary meristems. Although a high degree of sequence diversity was observed among putative SAP11 effectors identified from evolutionarily distinct clusters of phytoplasmas, these effectors acquired fundamental activity in destabilizing TB/CYC-TCPs. In addition, we demonstrate that miR156/SPLs and miR172/AP2 modules, which represent key regulatory hubs involved in plant phase transition, were modulated by Aster Yellows phytoplasma strain Witches' Broom (AY-WB) protein SAP11. A late-flowering phenotype with significant changes in the expression of flowering-related genes was observed in transgenic Arabidopsis plants expressing SAP11AYWB . These morphological and molecular alterations were correlated with the ability of SAP11 effectors to destabilize CIN (CINCINNATA)-TCPs. Although not all putative SAP11 effectors display broad-spectrum activities in modulating morphological and physiological changes in host plants, they serve as core virulence factors responsible for the witches' broom symptom caused by phytoplasmas.